Effects of NaCl content and drying temperature on lipid oxidation, protein oxidation, and physical properties of dry‐cured chicken. Issue 6 (27th May 2020) - Qu, Cheng; He, Zhifei; Wang, Zhaoming; Li, Shaobo; Wang, Zefu; Li, Hongjun
Abstract : Abstract: This study aimed to investigate the effects of different NaCl content and drying temperatures on the lipid oxidation, protein oxidation, and physical properties of dry‐cured chicken. In the final product, lipid oxidation, protein oxidation, and physical properties were significantly affected by NaCl and temperature. Increased NaCl content and temperature led to significantly increased level of indicators including conjugated diene, thiobarbituric acid reactive substances, and carbonyl contents ( P < 0.05). Conversely, the sulfhydryl contents and surface hydrophobicity significantly decreased ( P < 0.05). Results of sodium dodecyl sulfate polyacrylamide gel electrophoresis further indicated that NaCl and temperature affected protein oxidation and degradation. According to the drying curve, the main factor affecting the drying time was the drying temperature and a slower rate of moisture loss occurred in samples with higher NaCl content. Moreover, due to the effects of temperature on lipid and protein oxidation and moisture diffusion, the hardness and shrinkage ratio increased with temperature. Practical Application: Dry‐cured chicken is a kind of air‐dried meat product. During actual production of dry‐cured chicken, its physicochemical characteristics (e.g., lipid and protein oxidation and texture) are affected by NaCl content and drying temperature. In this study, the NaCl content and drying temperature were found to promote lipid and protein oxidation and have significant effects on texture properties. Therefore, the NaCl content and drying temperature should be controlled to improve the quality of dry‐cured chicken.